2021
DOI: 10.1097/md.0000000000026786
|View full text |Cite
|
Sign up to set email alerts
|

The changes of Lp-PLA2 in patients with gestational diabetes and its clinical significance

Abstract: Gestational diabetes mellitus (GDM) is one of the most common complications of pregnancy and associated with adverse pregnancy outcomes. The aim of this study was to investigate the changes of lipoprotein-associated phospholipaseA2 (Lp-PLA2) level and its correlation with biochemical indexes in patients with GDM.This observational cross-sectional study was performed among 52 GDM and 48 healthy pregnant women. Automatic biochemical analyzer was employed to test the biochemical indexes, including fasting plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…This increased fatty acid β-oxidation produced a large amount of acetyl-CoA, thus leading to a significant increase in TC synthesis and a decrease in HDL-C synthesis. 25,26 These findings were consistent with what we have found regarding the changes in lipid profiles in patients with GDM (Table 1). We further investigated the relationship between ATG7 levels and TG levels, LDL-C levels, TC levels, and HDL-C levels in patients with GDM.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This increased fatty acid β-oxidation produced a large amount of acetyl-CoA, thus leading to a significant increase in TC synthesis and a decrease in HDL-C synthesis. 25,26 These findings were consistent with what we have found regarding the changes in lipid profiles in patients with GDM (Table 1). We further investigated the relationship between ATG7 levels and TG levels, LDL-C levels, TC levels, and HDL-C levels in patients with GDM.…”
Section: Discussionsupporting
confidence: 91%
“…This decreased lipoprotein lipase activity reduced TG degradation and increased TG levels and LDL-C levels in the blood. 25 , 26 However, there was higher fatty acid β-oxidation activity in patients with GDM than in patients without GDM. This increased fatty acid β-oxidation produced a large amount of acetyl-CoA, thus leading to a significant increase in TC synthesis and a decrease in HDL-C synthesis.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies suggested that copper is tightly associated with liver cirrhosis and development of HCC, and with the survival of HCC patients [19,25,46]. To investigate the role of copper metabolism in HCC, we searched GSEA website online with the keyword "copper" and identified 14 copper metabolismrelated pathways containing 134 unique genes (Supplementary Tables 2, 3).…”
Section: Distinct Features Of Hcc In Copper Metabolismrelated Pathwaysmentioning
confidence: 99%
“…Except for its aforementioned functions under physiological processes, copper also involves in the tumorigenesis and development of HCC. An early study indicated that copper contents correlated with liver cirrhosis and HCC, and serum Cu levels might be helpful in detecting HCC [25]. Besides, high level of serum copper was associated with shorter survival of HCC patients [19,26].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that higher serum copper levels are associated with poorer survival in liver cancer [10]. According to previous research, liver copper content is closely associated Ivyspring International Publisher with hepatocellular carcinoma [11], The metabolism of copper affects the microenvironment of tumors as well. Hepatocellular carcinoma (HCC) still lacks a clear understanding of the mechanisms that cause cuproptosis.…”
Section: Introductionmentioning
confidence: 98%